Disaster Relief by Ship: Challenges and Responses Obtained from Disaster Relief Experience - Kunieda, Yoshiaki; Nunome, Akihiro; Kanayama, Emi; Chotechaung, Naruphun (Advances in Social Sciences Research Journal, 2025)
This study focused on the disaster relief activities carried out by the training ship Wakashio Maru in the wake of the 2024 Noto Peninsula Earthquake and it examined the characteristics and effectiveness of the ships, as well as the challenges related to disaster relief. Ships can perform a variety of roles in response to disasters, such as by transporting large quantities of supplies and personnel from the sea to areas where ground transportation is difficult or impossible, providing evacuation shelters and medical support and serving as communication hubs. In particular, the self-sufficient lifeline functions of large ferries and training ships, as well as the mental health care that they can provide to disaster victims, are strengths that other modes of transportation do not have. However, there are also challenges that are specific to ships, such as berthing restrictions, weather and sea conditions and limitations of their cargo-handling equipment. We note that to provide effective disaster relief, it is essential to conduct training and prepare equipment in advance and to establish information sharing systems with local governments and related organisations.